ANALISIS KEBUTUHAN PERANCANGAN PICTURE BOOK AUGEMENTED REALITY PENGENALAN PARTUTURAN BATAK TOBA - Hartono, Vivianty; Sihombing, Riama Maslan (Universitas Mercu Buana, 2023)
The Toba Batak ethnicity has a kinship system that becomes their cultural identity and way of life, known as Dalihan Na Tolu. Every Toba Batak needs to know two kinship systems in this philosophy: Tarombo Batak and Partuturan. After conducting research, it found that Toba Batak parents tend to teach Partuturan to their children as a basis they must know before exploring Dalihan Na Tolu. However, the Partuturan can be complicated for children to understand because it has many complex classifications. On the other hand, using verbal and observation to introduce this culture is also a problem that makes it more difficult for children to understand the Partuturan. This study aims analyze the method of introducing Partuturan using picture books and augmented reality. The methodology is mix-method in the form of interview data, literature study, and questionnaires in the form of open-ended questions. The implications of this study can be helpful for other researchers in understanding the design process of Partururan for Batak Toba children to foster a solid cultural identity using picture books based on augmented reality.